Pembuatan Cocopeat sebagai Media Tanam dalam Upaya Peningkatan Nilai Sabut Kelapa - Ari Kuntardina; Widya Septiana; Qirana Wahida Putri (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2022)
Coconut coir waste in Bojonegoro city market, Bojonegoro subdistrict, Bojonegoro regency causes its own problems. Solutions to overcome it by processing coconut coir waste into products that have benefits and selling value. One alternative is to process coconut coir into cocopeat. Coconut coir is the outer skin of the coconut fruit. Coconut coir is mostly only stacked after the meat is taken. This happens because of the lack of public awareness to manage the waste of coconut coir. By looking at the source of raw materials that are abundant and have not been utilized optimally. This is the reason in the manufacture of Cocopeat for the increase in added value of coconut coir as a planting medium. By converting coconut coir waste into planting media will reduce environmental pollution and can add economic value to the surrounding community. The purpose of this study is to find out the potential of coconut coir waste as a planting medium. The result of the activity is a solution to utilize coconut coir waste into a planting medium that has been packaged and ready for sale. Keywords: Coconut Coir Waste, Planting Media, Economic Value